2010
DOI: 10.1038/jcbfm.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Gap Junctions after Focused Ultrasound Blood–Brain Barrier Opening in the Rat Brain

Abstract: Ultrasound-induced opening of the blood-brain barrier (BBB) is an emerging technique for targeted drug delivery to the central nervous system. Gap junctions allow transfer of information between adjacent cells and are responsible for tissue homeostasis. We examined the effect of ultrasoundinduced BBB opening on the structure of gap junctions in cortical neurons, expressing Connexin 36, and astrocytes, expressing Connexin 43, after focused 1-MHz ultrasound exposure at 1.25 MPa of one hemisphere together with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 40 publications
(62 reference statements)
2
38
1
1
Order By: Relevance
“…31 Other groups reported the reorganization of connexin-43 in astrocytic gap junctions but no change in connexin-43 protein levels in response to injury. 32,33 Therefore, connexin-43 may be reorganized in CADASIL mice, which would correlate nicely with the reorganization of polarized markers of astrocytic end-feet. Using in vivo imaging, we also found that cerebral flood flow is not altered in TgNotch3 R169C mice at 7 months of age, despite significant changes in microvascular morphology changes at this age.…”
Section: Discussionmentioning
confidence: 78%
“…31 Other groups reported the reorganization of connexin-43 in astrocytic gap junctions but no change in connexin-43 protein levels in response to injury. 32,33 Therefore, connexin-43 may be reorganized in CADASIL mice, which would correlate nicely with the reorganization of polarized markers of astrocytic end-feet. Using in vivo imaging, we also found that cerebral flood flow is not altered in TgNotch3 R169C mice at 7 months of age, despite significant changes in microvascular morphology changes at this age.…”
Section: Discussionmentioning
confidence: 78%
“…Several potential cellular mechanisms for FUS-enhanced paracellular transport have been proposed, such as disassembling of tight junction proteins, 29 disruption of the interaction between tight junction proteins, 30 or reorganization of gap junction proteins. 31 The effect of FUS upon tight junctions has been reported to be transient and reversible. [29][30][31] Future studies are needed to elucidate how FUS and MBs interact at the molecular level of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a completely separate and additional advantage of such LCM/ND lipid nanoemulsion(s), as a component of this combination therapeutic, stems from the characteristic lipid-coated microbubble subpopulation (D'Arrigo 2011) existing in this nanoemulsion type. Specifically, such preformed (lipidstabilized) microbubbles are well known to substantially reduce the acoustic power levels needed for accomplishing temporary noninvasive (transcranial) ultrasound treatment Alonso et al 2010;Alonso et al 2011;Aslund et al 2017;Bing et al 2014;D'Arrigo 2015;Delalande et al 2013;Goliaei et al 2015;Kotopoulis et al 2013;Kotopoulis et al 2014;Lammers et al 2015;Marquet et al 2011;Meairs 2015;Meng et al 2017;Miller and O'Callaghan 2017), or sonoporation (Aubry et al 2016;Bouakaz et al 2016;Burgess and Hynynen 2016;Castle and Feinstein 2016;Delalande et al 2015;Horodyckid et al 2016;O'Reilly et al 2017;Paefgen et al 2015;Qin et al 2016;Sennoga et al 2016), if additionally desired for the Alzheimer's patient.…”
Section: Resultsmentioning
confidence: 99%